(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Language barriers present a persistent challenge in multilingual classrooms, often hindering students’ access to educational content and participation in learning. This study explores the use of Artificial Intelligence (AI) tools to reduce these barriers and enhance learning outcomes for multilingual students in English-medium education. Through a mixed-method approach involving case studies, surveys, and classroom observations across multiple international schools, the research examines the effectiveness of AI-based translation, speech recognition, real-time feedback, and personalized language instruction. The results demonstrate that AI tools can significantly improve communication, comprehension, and academic engagement among multilingual learners. The paper also discusses limitations related to equity, data privacy, and overdependence on technology.